Hybrid artificial intelligent systems : 13th International Conference, HAIS 2018, Oviedo, Spain, June 20-22, 2018, Proceedings - HAIS; Cos Juez, Francisco Javier de (Springer, 2018)
This volume constitutes the refereed proceedings of the 13th International Conference on Hybrid Artificial Intelligent Systems, HAIS 2018, held in Oviedo, Spain, in June 2018. The 62 full papers published in this volume were carefully reviewed and selected from 104 submissions. They are organized in the following topical sections: Neurocomputing, fuzzy systems, rough sets, evolutionary algorithms, Agents and Multiagent Systems, and alike